Keputusan bentuk visual dalam mendesain Self Service Kiosk - Rafi Ihsandiyumna; Andry Masri (Institut Seni Indonesia Yogyakarta, 2020)
Significant changes have occurred in the past decades from analogue or manual technology to digital technology which caused many industries to adapt or even transition to it. One of a product commodity which is the result of innovation caused by this change is self-service technology (SST). Currently, there aren’t so many industries of SSTs in Indonesia, but the concept is still feasible because it has characteristics that have high selling value and facilitate activities in commercial industry in general. This literature examines the important aspects which take effect and need to be considered in SST visual form decision making. The purpose of this research is to produce SST design through formalistic approach also as a tool for the analysis process in space, human, and business aspects. This research generates a product design which has harmony in the interaction with its surrounding objects’ visual characteristics.Keywords: innovation, self-service technology, formalistic, visual form decision